Analisis Potensi Biomassa di Kecamatan Pulau Burung Menggunakan Teknologi Insenerasi Sebagai Bahan Bakar Pembangkit Listrik Tenaga Uap - Suwitno Suwitno; Hendrian Syaputra; Nurhalim Nurhalim; Dian Yayan Sukma; Amir Hamzah (Universitas Islam Sumatera Utara, 2023)
Steam Power Plant is a widely applied electrical energy generation system. The limitation of fossil fuels has spurred us to find alternative fuels. One alternative fuel that can be used in PLTU is biomass. Coconut coir is a biomass that has the potential to become an alternative fuel which is abundantly available in Indragiri Hilir district, especially in the Pulau Burung sub-district. This study aims to calculate the electrical power generated from the utilization of coconut fiber as an energy source in Steam Power Plants. The method used in this research is to process quantitative data from coconut fruit production to obtain the availability of coconut fiber, generated calorific value, steam turbine output work and generated electrical energy. The results showed that the availability of coconut fiber with an annual average value of 1,058.405 kg/hour. The heat value from burning one kilogram of coconut fiber was 16,767.2967 kJ / kg. Using calculations, two steam power plant of electrical system designs were obtained, where the output power of the first unit generator was 647,7053 kW and the output of the unit two generating system is 289,2458 kW with a total electric power generated by the PLTU of 936.9511 kW.